Recent Advances in DNA Systems for In Situ Telomerase Activity Detection and Imaging - Shiyi Zhang; Wenjing Xiong; Shuyue Xu; Ruocan Qian (Chemosensors)
Telomeres play a key role in maintaining chromosome stability and cellular aging. They consist of repetitive DNA sequences that protect chromosome ends and regulate cell division. Telomerase is a reverse transcriptase enzyme counteracts the natural shortening of telomeres during cell division by extending them. Its activity is pivotal in stem cells and cancer cells but absent in most normal somatic cells. Recent advances in biosensor technologies have facilitated the in situ detection of telomerase activity, which is essential for understanding its role in aging and cancer. Techniques such as fluorescence, electrochemistry, and DNA nanotechnology are now being employed to monitor telomerase activity in living cells, providing real-time insights into cellular processes. DNA-based biosensors, especially those incorporating molecular beacons, DNA walkers, and logic gates, have shown promise for enhancing sensitivity and specificity in telomerase imaging. These approaches also facilitate the simultaneous analysis of related cellular pathways, offering potential applications in early cancer detection and precision therapies. This review explores recent developments in intracellular telomerase imaging, highlighting innovative approaches such as DNA-functionalized nanoparticles and multi-channel logic systems, which offer non-invasive, real-time detection of telomerase activity in complex cellular environments.